Factors Influencing the Achievement of the Budget Implementation Performance Indicator (IKPA) Values Working Units in the Work Area of KPPN Medan II - Daniel Simanjuntak; Iskandar Muda Damanik; Abdillah Arif Nasution (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This study aims to determine the factors that influence the achievement of the Budget Implementation Performance Indicator (IKPA) value of the Work Unit in the Medan II KPPN Work Area. The Budget Implementation Performance Indicator (IKPA) is an indicator set by the Ministry of Finance as BUN which is used as a measure and reflects the performance of the work unit on the quality of budget planning, the quality of budget implementation and the quality of budget implementation results. This study aims to determine what factors influence the achievement of the IKPA value in the work unit at the Medan II KPPN. This research method uses a quantitative approach with primary data through the distribution of questionnaires to employees who play a role in the achievement of the Satker IKPA, namely PPK, PPSPM, Treasurer, Budget Operator and Commitment/Payment Operator. The study population consisted of 170 Work Units, while the sample of this study was 200 respondents conducted in 40 Work Units in the Medan II KPPN work area with the criteria of Work Units that obtained IKPA value achievements in the sufficient and less categories for the 2022 to 2024 budget years. Hypothesis testing used analysis with the help of SmartPLS 4. The results of the study showed that transparency, organizational commitment, human resource competence, government regulations and coordination had a positive and significant effect on the achievement of IKPA values. This finding confirms the importance of transparency in state financial management accompanied by organizational commitment, increasing human resource competence, compliance with government regulations and increasing coordination between Work Units and Medan II KPPN which play a role in increasing the achievement of IKPA values ​​of Work Units